Bioactive gel-glasses with distinctly different compositions: Bioactivity, viability of stem cells and antibiofilm effect against Streptococcus mutans - Siqueira, Renato L.; Maurmann, Natasha; Burguez, Daniela; Pereira, Daniela P.; Rastelli, Alessandra N. S. [UNESP]; Peitl, Oscar; Pranke, Patricia; Zanotto, Edgar D. (Elsevier B.V., 2017)
In this study, an evaluation was performed to determine the in vitro bioactivity, viability of stem cells, and antibiofilm effect against Streptococcus mutans of two bioactive gel-glass 60SiO(2)-36CaO-4P(2)O(5) (BG-A) and 80SiO(2)-15CaO-5P(2)O(5) (BG-B) compositions. Both materials were bioactive and undergo the formation of hydroxycarbonate apatite (HCA) on their surfaces when immersed in simulated body fluid (SBF) after 12 h, but the BG-A composition showed a more significant formation rate. The pH variation of the samples during the test in SBF indicated that an abrupt change had occurred for the BG-A composition within the first few hours, and the pH was subsequently maintained over time, supporting its stronger antibacterial effects against S. mutans. For the in vitro viability test using mesenchymal stem cells (MSCs), the BG-B showed significantly higher cell viability compared to the BG-A composition at concentrations of 0.125, 1.25 and 12.50 mg/mL for 2 days. These results indicated that the higher solubility of the BG-A glass favors bioactivity and antibacterial effects. However, as a result of rapid degradation, the increase in the concentration of ions in the cell culture medium was not favorable for cell proliferation. Thus, by varying the composition of glasses, and consequently their dissolution rate, it is possible to favor bioactivity, antimicrobial activity or stem cell proliferation for a particular application of interest. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Bioactive glass; Sol-gel; In vitro bioactivity; Cell viability; Stem cells; Biofilm